ECO-PRINTING AS ALTERNATIVE OPPORTUNITY OF SCHOOL-BASED-MSME ENVIRONMENTALLY FRIENDLY - Erva Elli Kristanti (Pedagogic Research-Applied Literacy Journal, 2024)
The textile industry was one of the contributors to the highest amount of waste in the world. One of the wastes produced by the textile industry was liquid waste which came from the remains of synthetic dyes which contained several dangerous chemicals. An alternative that could be done to reduce liquid waste from synthetic dyes was to switch to using natural dyes (environmentally friendly) that came from plants. One technique that could be used to color textiles was the eco-printing technique. The eco-print technique was a process for transferring color and shape through direct contact. The eco-printing technique used materials from plant parts that contained color pigments such as leaves, flowers, bark, etc. Products produced from eco-printings could be a school-based-MSME opportunity because eco-printings had artistic value and high selling value. The research method used literature study by taking reference sources from journals. The purpose of writing this article was to describe eco-printing as a business opportunity that could be pioneered by schools as a project continually.